1997
DOI: 10.1152/jn.1997.77.4.1697
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Subthreshold Membrane Potential Fluctuations and Action Potential Variability of Rat Corticostriatal and Striatal Neurons In Vivo

Abstract: We measured the timing of spontaneous membrane potential fluctuations and action potentials of medial and lateral agranular corticostriatal and striatal neurons with the use of in vivo intracellular recordings in urethan-anesthetized rats. All neurons showed spontaneous subthreshold membrane potential shifts from 7 to 32 mV in amplitude, fluctuating between a hyperpolarized down state and depolarized up state. Action potentials arose only during the up state. The membrane potential state transitions showed a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
323
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(371 citation statements)
references
References 34 publications
46
323
2
Order By: Relevance
“…Similar dynamics have been described in vitro in the presence of near normal Ca 2+ /high K + /low Mg 2+ , either spontaneously or in response to electrical stimulation of the cortex (Shu et al, 2003;Steriade et al, 1993b;Sanchez-Vives and McCormick, 2000), and during application of either mGluR agonists or muscarinic agonists (Beierlein et al, 2000). It has been suggested that both intrinsic cellular and network mechanisms are crucial for the slow oscillations (Wilson et al, 1990;Stern et al, 1997;Shu et al, 2003;Sanchez-Vives and McCormick, 2000) but the necessary and sufficient conditions that determine its frequency (the duration of UP and DOWN states) are still debated. The UP state is accompanied by the synchronous recruitment of numerous cells in the network and changes in input resistance Shu et al, 2003;Waters and Helmchen, 2006).…”
Section: Slow (<1 Hz) Rhythms-mirceasupporting
confidence: 56%
See 1 more Smart Citation
“…Similar dynamics have been described in vitro in the presence of near normal Ca 2+ /high K + /low Mg 2+ , either spontaneously or in response to electrical stimulation of the cortex (Shu et al, 2003;Steriade et al, 1993b;Sanchez-Vives and McCormick, 2000), and during application of either mGluR agonists or muscarinic agonists (Beierlein et al, 2000). It has been suggested that both intrinsic cellular and network mechanisms are crucial for the slow oscillations (Wilson et al, 1990;Stern et al, 1997;Shu et al, 2003;Sanchez-Vives and McCormick, 2000) but the necessary and sufficient conditions that determine its frequency (the duration of UP and DOWN states) are still debated. The UP state is accompanied by the synchronous recruitment of numerous cells in the network and changes in input resistance Shu et al, 2003;Waters and Helmchen, 2006).…”
Section: Slow (<1 Hz) Rhythms-mirceasupporting
confidence: 56%
“…The DOWN state is associated with a positive polarity local field potential (LFP) in infragranular layers. Rhythmical shifts between DOWN and UP states have also been described in striatal (Wilson et al, 1990;Stern et al, 1997) and thalamic (Steriade et al, 1993b;Timofeev and Steriade, 1996;Hughes et al, 2002) neurons. Similar dynamics have been described in vitro in the presence of near normal Ca 2+ /high K + /low Mg 2+ , either spontaneously or in response to electrical stimulation of the cortex (Shu et al, 2003;Steriade et al, 1993b;Sanchez-Vives and McCormick, 2000), and during application of either mGluR agonists or muscarinic agonists (Beierlein et al, 2000).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 92%
“…Membrane potential fluctuations were usually recorded in anesthetized animals but also occur in awake animals with a less regular frequency (Wilson and Groves, 1981;Wilson, 1993). Increased activity of corticostriatal neurons seems to induce transitions to the up-state and to maintain the up-state (Wilson and Kawaguchi 1996;Stern et al 1997). In vivo stimulation of the cortex resets the phase of the oscillation (Katayama et al, 1980).…”
Section: Striatal Membrane Potential Fluctuationsmentioning
confidence: 98%
“…5B) (Wilson and Kawaguchi 1996;Stern et al 1997;Wickens and Wilson 1998). Membrane potential fluctuations were usually recorded in anesthetized animals but also occur in awake animals with a less regular frequency (Wilson and Groves, 1981;Wilson, 1993).…”
Section: Striatal Membrane Potential Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation